Use of acquired skills by returnee labor migrants in the home country - Regmi, Krishna Kumar (Butwal Campus Journal, 2024)
The study examined the use of newly acquired skills by returning migrant workers in Nepal. It was found that only one-third of the returnees worked in similar occupations to their native country, and two-thirds were deskilled due to difficulties in applying their skills. Self-employed individuals accounted for over one-third of returns, indicating a desire to operate their own firm. Both genders used the acquired skills in statistically insignificant ways, but the difference between wage-employed and self-employed individuals was significant. The study also found that administrative, political, economic, and technological obstacles hindered the returnees' reintegration into society. The study suggests that if returnees are employed in a related field, the human capital they gained in the host nation adds value to their employment. However, most returnees were unable to use their newly acquired talents due to not being hired for similar positions upon their return. To contribute to the country's economic progress, politicians must create programs and policies to protect returnees from losing their skills.